Deteksi Anemia pada Ibu Hamil Mengunakan Metode Non Invasif Berbasis Kecerdasan Artifisial - Hajrianti, Siti; Widyawati, Melyana Nurul; Kurnianingsih, Kurnianingsih (Journal of Telenursing (JOTING), 2023)
This study aims to create a non-invasive tool for anemia detection in pregnant women based on artificial intelligence. The method used is Research and Development (R&D) with small-scale tests. The results showed that a non-invasive anemia detection tool was feasible to use because it got an AUC value of 91% which was good in the diagnostic test of the tool and the sensitivity value of the tool was 94% which means the tool is feasible to use. In addition, it can determine anemia status in pregnant women with a value of (p -value 0.957). Conclusion, the design of a non-invasive anemia detection tool based on artificial intelligence is feasible and provides valid and fast results in measuring Hb levels in determining anemia status in pregnant women. Keywords: Anemia, Artificial Intelligence, Hemoglobin